Positive I-123-MIBG-Scintigraphy in Osteosarcoma - von der Hardt, K.; Bair, H.-J.; Kirchner, T.; Feistel, H.; Beck, J. (Nuklearmedizin - NuclearMedicine, 1998)
I-123-MIBG scintigraphy has become a standard imaging technique in the detection of neuroendocrine or neurocrest derived tumors, especially neuroblastoma and pheochromocytoma. We report on a positive I-123-MIBG uptake in a pediatric osteosarcoma patient and demonstrate, that unusual results still occur with this established imaging method.
Keywords: I-123-MIBG scintigraphy; osteosarcoma; pediatric